Tectonics of the North African Variscides (Morocco, western Algeria): an outline - Hoepffner, Christian; Houari, Mohamed Rachid; Bouabdelli, Mohamed (Comptes rendus. Geoscience, 2006)
The Palaeozoic terranes that crop out north of the South Atlasic Line constitute the Variscan Belt of North Africa. Subdivision of the belt into five structural zones separated by major shear zones results from a polyphase evolution including very localised Prevariscan events (450-430 Ma), which correspond to the Caledonian cycle, and Variscan events involving three main stages: Eovariscan (370-360 Ma), Mesovariscan (330-320 Ma), and Neovariscan (300-290 Ma), followed by Tardi-Variscan events during Early Permian-Triassic times. During the Variscan evolution, the geodynamic context is transtensive-transpressive, and controls the opening and closure of Devono-Carboniferous basins. The Variscan deformations are accommodated by folding and combination of thrusting and strike-slip faulting associated with a low-grade to medium-grade metamorphic evolution, characteristic of the external zones of the orogens. The lack of oceanic crust, and thus of suture zone in the Palaeozoic series suggests that the North African Variscan Belt is an intracontinental part of the Variscan orogen, which evolved near the margin of the West African Craton. The links with the other Periatlantic Palaeozoic segments still remain a subject of discussion.